11.1: Invited Paper: Development of the World‐wide Largest 110′ 4K2K 3D TFT‐LCD Display. Issue 1 (1st July 2013) - Chen, Li‐Yi; Chen, Yu‐Yeh; Hou, Hung‐Lung; Mo, Yuming; Chiu, Chung‐Yi
Abstract CSOT has successfully developed 110‐inch LCD TV that is the largest LCD TV. It integrates many innovations in LCD technology, containing 50000:1 dynamic contrast ratio, 1000 nits ultra high brightness, high‐saturated color reproduction with NTSC 92% and 288 areas local dimming backlight. Moreover, Shutter‐glasses 3D function has also been achieved